“Why am I here?”Analyses of the values and meanings of higher education through the eyes of students - Samorodova, Ekaterina; Chitakhova, Liubov; Merzouk, Samira (Journal of Education Culture and Society, 2026)
Aim. The question of the value and meaning of higher education in the modern world, in the era of new technologies and opportunities, takes on a new meaning. What do future professionals expect from universities, what do they perceive as their meaning or points, and what kind of values ​​do they respect? This is the primary research question of the current study. The authors analysed the meanings, expectations, and values ​​of students at several humanities universities worldwide, as reflected in questionnaires, in order to answer this very question and identify the main reasons for pursuing higher education. Methods. The authors used comparative, contrastive, analytical, and systematic research methods. The main basis for obtaining the results were anonymous questionnaires and surveys, in the form of tests and open-ended questions. Results. The authors conducted an in-depth analysis of students’ reflections on the values ​​and meanings of higher education, their main reasons and needs for pursuing it. They also identified the main criteria by which the students’ answers and reflections were classified: pragmatic, social-status, and existential. Conclusions. The authors concluded that actually higher education at a university is not merely an end in itself nor the final milestone on the path to professional mastery by achieving professional competencies. Higher education is generally viewed as a process of self-improvement, self-determination, self-knowledge, and self-development, the primary foundation for developing the necessary competencies and skills needed to adapt to new conditions and create the architecture of one’s professional identity.